Synonymy of Ixodes aragaoi with Ixodes fuscipes, and reinstatement of Ixodes spinosus (Acari: Ixodidae) - Labruna, Marcelo B. (2020)
Ixodes fuscipes Koch, 1844, described from Brazil, has been considered a valid species with records from Brazil and Peru. Ixodes spinosus Neumann, 1899, also described from Brazil, has been considered a synonym of I. fuscipes. In 2014, Ixodes aragaoi Fonseca, 1935 was redescribed as a valid species for Brazil and Uruguay. Until the present study, one major difference between the females of I. fuscipes and I. aragaoi was the horn-like auriculae in the former versus the ridge-like auriculae in the later, but this morphological difference was not supported after examination of the holotype of I. fuscipes and a syntype female of I. spinosus. Surprisingly, we found the type of I. fuscipes to have ridge-like auriculae, in contrast to the horn-like auriculae of I. spinosus. Comparisons of the I. fuscipes holotype with the syntypes of I. aragaoi revealed that they correspond to the same species. Therefore, we redescribe I. fuscipes, relegate I. aragaoi to a junior synonym of I. fuscipes, and reinstate I. spinosus as a valid species. After examining all lots of I. fuscipes in four tick collections, no specimen was recognized as I. fuscipes when compared with the type specimen of this taxon. On the other hand, specimens previously identified as I. aragaoi are now confirmed as I. fuscipes, with bona fide records for Brazil and Uruguay. Some of the specimens previously reported as I. fuscipes are now confirmed as I. spinosus, with records in two Brazilian biomes, Amazon and Atlantic rainforest. We present lists of the ticks examined in this study, with their current taxonomic status.